Swarm Intelligent in Bio-Inspired Perspective: A Summary - Nyayu Husni Latifah; Ade Silvia; Ekawati Prihatini; Siti Nurmaini; Irsyadi Yani (Universitas Sriwijaya, 2018)
This paper summarizes the research performed in the field of swarm intelligent in recent years. The classification of swarm intelligence based on behavior is introduced. The principles of each behaviors, i.e. foraging, aggregating, gathering, preying, echolocation, growth, mating, clustering, climbing, brooding, herding, and jumping are described. 3 algorithms commonly used in swarm intelligent are discussed. At the end of summary, the applications of the SI algorithms are presented.